Simulation studies of mineral processing - Aziz, Badhrulhisham Abdul; Hisyam, Anwaruddin; Yunus, M. Y. M.; Cheng, Chin Kui; Nurul Ain, Ismail (2017)
All mineral processing exhibits complex operating behaviour and building quantitative models for these operations is not a straightforward task. In some cases, the basic fundamental principles of a particular type of process are ill understood. In most cases the complexity of the operation precludes any complete analysis of the physical and chemical processes. This work focuses on the development of hydrometallurgical simulator for critical metals such as rare earth and gold. Using Aspen Plus and HSC Chemistry software as the platform, simulation models were established based on various case studies from the literature. The simulators on; a) leaching of rare earth and b) extraction of gold were successfully presented. These models are able to predict the output of the leaching/extraction system from assorted ores. In mineral processing field, this models able to aid mineralogist to optimized the process in a cheaper and less time-consuming way.